Pembinaan Rohani Kategorial Anak-Anak dan Dewasa di GPPIK “Bukit Torsina” Runut, Kab. Landak, Kalimantan Barat - Blegur, Romelus; Gea, Leniwan Darmawati; Siging, Stevani; Linda, Linda; Anda, Matalius; Yudas, Andre; Oskaliandi, Oktavianus; Yosua, Yosua; Sardi, Sardi (Devotion: Jurnal Pengabdian Masyarakat, 2025)
This PkM activity is carried out in the context of spiritual formation for groups in the categories of children and adults. One of the focuses is serving children creatively. This is necessary because children's services experience problems in various churches, due to a lack of human resources, but also a lack of creativity in children's services which has an impact on reducing children's interest in attending worship services. These concerns prompted the STT ATI team to carry out PkM activities as a way to overcome them. The activity was carried out at GPPIK "Bukit Torsina" Runut, Landak Regency, West Kalimantan. The methods used in this PkM activity are stories, movements and songs, games, creations, and sermons or lectures. The results of this activity show that the activity had a good impact on the congregation and received a positive response from the local church. Apart from that, children learn new things through creative children's services. Services in the adult category also received a good response.